Properties of MnO doped graphene synthesized by co-precipitation method - Ilman Nur Sasongko, M.; Poppy Puspitasari; Sukarni; Cepi Yazirin (Functional Materials, 2018)
MnO doped graphene specimens were synthesized using a simple and cost-effective method, i.e. co-precipitation. The characterization of specimens was done through various techniques, such as X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Fourier Transform Infrared (FTIR). Single phase pattern on [222], crystallite size, and d-spacing were confirmed by XRD results. The nanostructure morphology was observed using SEM. FTIR showed the shifted peaks and changes in the intensity of molecular bonds of the material. The specimens were sintered for 1 h at various temperatures of 500 °C, 600 °C, and 700 °C. The XRD characterization showed that sintering at 700 °C resulted in MnO and GO peaks with the highest intensity, but the specimen sintered at 600 °C had the best grain size of 70.39 nm. The morphology characterization by SEM showed a change of shape from triangle to nanosphere with agglomeration. The results of FTIR showed that the shifts in C-O and Mn-O groups were followed by an increase in N-H, C-H, C=O, C-O, and Mn-O. The results of this study suggest that single-phase MnO doped graphene was successfully synthesized using the co-precipitation method.